Fast wave propagation in the gas insulation system - Azhar Khairuddin, 1963-, author; Hashim Shaibon, supervisor; Fakulti Kejuruteraan Elektrik (Kuala Lumpur : Universiti Teknologi Malaysia, 1991)
Thesis (Master in Electrical Engineering) - Universiti Teknologi Malaysia, 1991